Mango peel ingredient as salt and phosphate replacement in chicken breast marinade - Sunisa Roidoung; Napatsawan Ponta; Ruttapong Intisan (International Journal of Food Studies)
Whole mango peel powder and fibre extracted from mango peel were investigated as potential ingredients to replace salt and phosphate in chicken marinade. Whole mango peel powder possessed higher water absorption capacity than mango peel fibre, 4.57% and 1.47%, respectively (P < 0.05). Similar oil absorption capacity was observed in both mango peel ingredients (P > 0.05). Purified pectin and sorbitol syrup were also used to compare the water holding capacity in marinated chicken breasts. Mango peel ingredients exhibited less cooking loss than pectin and sorbitol syrup, however, higher cooking loss than sodium tripolyphosphate (STPP) and NaCl (P > 0.05). Marinating with mango peel ingredients significantly increased a* value of chicken breasts after cooking, while L* and b* values were similar in marinating with NaCl (P > 0.05). Hardness of frozen fully cooked chicken breast was measured after thawing. The lowest shear force of 7.13 N was observed in chicken breasts marinated with mango peel fibre (P < 0.05), while the hardness of chicken breasts marinated with whole mango peel powder was not significant different from STPP and NaCl treatments. Results from this study revealed a potential approach of utilizing fruit waste as an ingredient to substitute phosphate and salt in chicken marinade.